1992
DOI: 10.1111/j.1745-4581.1992.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION of MICROBIAL NUMBERS FROM PURE BACTERIAL CULTURES and FROM MINCED BEEF SAMPLES BY REFLECTANCE COLORIMETRY WITH OMNISPECTM 40001

Abstract: Tristimulus reflectance colorimetry (RC) is a rapid method with which microbial activities can be monitored by the mediation of dye pigmentation changes. Dyes that produce color changes because of shifts of pH and oxidation/reduction (O/R) potential or free amino groups can be used. To estimate total microbial numbers from pure coliform and Listeria cultures and from minced beef samples, the appropriate color endpoint values were selected for each sample type (b*=+2 for coliforms, L*=+ 11 for Listeria, and a*=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…OmniSpec Bioactivity System Figure 1 shows the times required for serial dilutions of L. monocytogenes Scott A to decrease the L* color values from 18 to 4. The color values changed from light yellow to black according to the hydrolysis of esculin in Fraser broth, and L* = + 11 was the suitable endpoint value for all Listeria strains (Manninen and Fung 1992). Each dilution curve was separated clearly and perpendicular to the x-axis at L* = 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OmniSpec Bioactivity System Figure 1 shows the times required for serial dilutions of L. monocytogenes Scott A to decrease the L* color values from 18 to 4. The color values changed from light yellow to black according to the hydrolysis of esculin in Fraser broth, and L* = + 11 was the suitable endpoint value for all Listeria strains (Manninen and Fung 1992). Each dilution curve was separated clearly and perpendicular to the x-axis at L* = 11.…”
Section: Resultsmentioning
confidence: 99%
“…To enumerate the bacteria before each test. 0.1 mi of the pure culture suspension was spread in duplicate onto BHI and modified Oxford (MOX) agar plates (McClain and Lee 1989) and incubated at 37C with 30 min reading interval for 48 h. The color value for the determination of a CDT was at L* = I 1 (Manninen and Fung 1992) with color change from L* = 20 to 3 (light yellow to black). Each membrane fraction was used in amounts equivalent to the activity of Oxyrase at 0.1.…”
Section: Food Pathogensmentioning
confidence: 99%
“…The change of color or hue (a*, b*, L*) can be monitored similar to impedance and conductance curve. Manninen and Fung (1992b) evaluated this system in a study of pure cultures of Listeria monocytogenes and food samples and found high correlation coefficients (r) of 0.90 to 0.99 for pure cultures and 0.82 for minced beef between the colony counts predicated by the colorimetric technique and the results of the traditional plate count method. They also showed that detection times for bacterial cultures were substantially (2 to 24 h) shorter using the instrument and concluded that the Omnispec system simplifies the analyses, saves labor and materials and provides a high sample capacity.…”
Section: Real-time Hygiene Monitoring Systems Widely Usedmentioning
confidence: 99%